Safety and efficacy of mycophenolate mofetil in treating neuromyelitis optica spectrum disorders: a protocol for systematic review and meta-analysis - Yang Chen; Ming Jin; Mengyu Han; Luqi Nong; Ziqiang Liu; You Chen; Huan Meng; Yali Qin; Zhijun Wang (BMJ Open)
Introduction Neuromyelitis optica spectrum disorders (NMOSD) is an inflammatory and heterogeneous astrocyte disorder of the central nervous system with the characteristic of higher incidence in women and Asian people. Most patients with NMOSD have a course of recurrence and remission that is prone to cause paralysis and blindness. Several studies have confirmed the efficacy and promising prospect of mycophenolate mofetil (MMF) in the treatment of NMOSD. Yet its therapeutic effect and safety are controversial. Although there has been two published literature that is relevant to the topic of this study, both of them have certain defects, and they can only provide answers about the efficacy or safety of MMF in the treatment of NMOSD from partial perspectives or conclusions. This research aims to perform a direct and comprehensive systematic review and meta-analysis to evaluate MMF’s effectiveness and safety in treating NMOSD.Methods and analysis This systematic review will cover all comparative researches, from randomised controlled trials to cohort studies, and case–control study. A relevant literature search will be conducted in PubMed, Web of Science, EMBASE, the Cochrane Library, China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database and Chinese Biomedical Literature Database from their inception to 31 June 2020. We will also search registers of clinical trials, potential grey literature and abstracts from conferences. There are no limits on language and publication status. The reporting quality and risk of bias will be assessed by two researchers independently. Expanded Disability Status Scales and annualised relapse rate will be evaluated as the primary outcome. The secondary outcomes will consist of the frequency and severity of adverse events, best-corrected visual acuity, relapse-free rate and time to the next attack. A meta-analysis will be performed using RevMan V.5.3 software provided by the Cochrane Collaboration and Stata V.12.0.Ethics and dissemination Because the data used for this systematic review will be exclusively extracted from published studies, ethical approval and informed consent of patients will not be required. The systematic review will be published in a peer-reviewed journal, presented at conferences and will be shared on social media platforms.PROSPERO registration number CRD42020164179.